Antibiotic prescriptions associated with a diagnosis of acute nasopharyngitis by general GPs in France: a retrospective study - Tran Tue Duong; Matta Matta; Beranger Lekens; Sylvain Diamantis (BJGP Open)
Background: Nasopharyngitis is a common viral infection that has led to an overuse of prescription drugs, in particular antibiotics, which are not indicated for this condition. Aim: The purpose of this study was to describe drug prescriptions for patients with a diagnosis of acute rhinopharyngitis in general practices in France. Design & setting: Retrospective study of 1 067 403 prescriptions for a diagnosis of nasopharyngitis issued by 2637 physicians to 754 476 patients living in metropolitan France. Method: The data were sourced from the prescription software, Cegedim, for the period 1 January 2018 to 31 December 2021 and analysed according to patients’ and physicians’ ages. Results: A total of 2 591 584 medications were prescribed by GPs, with a median of three medications per patient. A total of 171 540 courses of antibiotics were prescribed (16% prescription rates), with amoxicillin being the most frequently prescribed (102 089 prescriptions; 59.5% of antibiotic prescriptions). Amoxicillin prescription increased in extreme age groups (18.2% of visits in those aged 9 years and under, and 10.0% of visits in those aged over 80 years, while patients aged 20–29-years were prescribed amoxicillin in just 2.9% of visits), and more prescriptions are issued by older doctors (GPs older than 70 years prescribed antibiotics in 26.4% of visits versus 3.2% of visits by GPs aged under 29 years). Conclusion: Nasopharyngitis is frequently a cause of therapeutic over-prescriptions including antibiotics, with an antibiotic prescription rate of 16%. Additional research is required to enhance our understanding of factors linked to drug prescriptions.